The carnivorous digestive system and bamboo diet of giant pandas may shape their low gut bacterial diversity. Issue 1 (13th March 2020) - Guo, Wei; Chen, Yinfeng; Wang, Chengdong; Ning, Ruihong; Zeng, Bo; Tang, Jingsi; Li, Caiwu; Zhang, Mingwang; Li, Yan; Ni, Qingyong; Ni, Xueqin; Zhang, Hemin; et al.
Abstract: : The gut microbiota diversity of eight panda cubs was assessed during a dietary switch. Gut microbiota diversity of panda cubs significantly decreased after bamboo consumption. Carnivorous species living on a plant-based diet possess low microbial diversity. Mice were fed a bamboo diet but did not display low gut microbiota diversity. : Giant pandas have an exclusive diet of bamboo; however, their gut microbiotas are more similar to carnivores than herbivores in terms of bacterial composition and their functional potential. This is inconsistent with observations that typical herbivores possess highly diverse gut microbiotas. It is unclear why the gut bacterial diversity of giant pandas is so low. Herein, the dynamic variations in the gut microbiota of eight giant panda cubs were measured using 16S rRNA gene paired-end sequencing during a dietary switch. Similar data from red panda (an herbivorous carnivore) and carnivorous species were compared with that of giant pandas. In addition, mice were fed a high-bamboo diet (80% bamboo and 20% rat feed) to determine whether a bamboo diet could lower the gut bacterial diversity in a non-carnivorous digestive tract. The diversity of giant panda gut microbiotas decreased significantly after switching from milk and complementary food to bamboo diet. Carnivorous species living on a plant-based diet, including giant and red pandas, possess a lower microbial diversity than other carnivore species. Mouse gut microbiota diversity significantly increased after adding high-fibre bamboo to their diet. Findings suggest that a very restricted diet (bamboo) within a carnivorous digestive system might be critical for shaping a low gut bacterial diversity in giant pandas. Abstract : The gut microbiota diversity of eight panda cubs was assessed during a dietary switch. Gut microbiota diversity of panda cubs significantly decreased after bamboo consumption. Carnivorous species living on a plant-based diet possess low microbial diversity. Mice were fed a bamboo diet but did not display low gut microbiota diversity.